Ordinary State Administrative Dispute and Positive-Fictitious decisions Dispute in Administrative Court (PTUN), In Relation to Administrative Appeal - Weda Kupita (Faculty of Law, Universitas Jenderal Soedirman, 2021)
The State Administration decisions, is a written determination by a government official, if it is the object of a dispute in the Administrative Court, it is categorized as an